Evaluation of a novel bacterial biomass as a substitution for soybean meal in plant‐based practical diets for Pacific white shrimp Litopenaeus vannamei. (20th September 2017) - Qiu, X.; Tian, H.Y.; Davis, D.A.
Abstract: Three growth trials and a digestibility trial were designed to evaluate the efficacy of a novel bacterial biomass (BB) in commercial‐type feed formulation for Pacific white shrimp, Litopenaeus vannamei . In trial 1, the basal diet was supplemented with 0, 60 and 120 g/kg BB to replace soybean meal (SBM). Significant improvement was observed in the survival when BB was incorporated in the diets. However, shrimp fed diets containing 120 g/kg BB exhibited significantly lower weight gain (WG) and higher feed conversion ratio (FCR). To confirm the results from trial 1 and explore the effects of BB supplementation at low levels, the basal diet was incorporated with 0, 10, 20, 40, 60 and 120 g/kg BB to replace SBM in trial 2. Significant reductions in WG, FCR, lipid content of whole body, protein retention efficiency and most amino acids retention efficiency were detected in shrimp fed with diet containing 120 g/kg BB. Trial 3 was designed to elucidate whether the digestible protein is the cause of reduced growth. No improvements in terms of growth performance and FCR were detected in the treatments balanced for digestible protein. Apparent digestibility coefficients of energy, protein and amino acid (AA) for BB were determined using chromic oxide as an inert marker and the 70:30 replacement technique. The energy, protein and individual amino acid digestibility coefficients of BB were significantly lower than those of fish meal (FM) and SBM that were given at the same time. Results of this study indicated that BB can be utilized up to 40 g/kg in shrimp feed without causing a decrease in growth. However, supplementations (≥60 g/kg) of BB can result in negative effects on growth response, FCR and protein as well as amino acids retention efficiency. At the lower levels of inclusion, shrimp performance was improved when BB was supplemented on a digestibility basis; however, at the higher level of inclusion, there was no improvement, indicating there may be other nutrients limiting. Based on enhanced survival in the treatment with BB supplementation in trial 1, further research regarding the immune effects of BB in practical shrimp feed will be necessary.